2016
DOI: 10.1515/prolas-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Herpesviruses 6 and 7 Infection on the Clinical Course of Rheumatoid Arthritis / Cilvēka Herpesvīrusa 6 Un 7 Infekcijas Ietekme Uz Reimatoīdā Artrīta Klīnisko Gaitu

Abstract: Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disease affecting joints and causing symmetrical chronic progressive aseptic synovitis and erosive-destructive changes. Viruses and viral infections are considered to be the main risk factors for autoimmune disease development (especially for individuals with genetic predisposition). The goal of this study was to evaluate the frequency of HHV-6 and HHV-7 persistent infection and its activity phase in RA and osteoarthritis (OA) patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Another study demonstrated that HHV-6 DNA could be detected in synovial tissues and fluid, and antigens could be visualized in synovial tissues of RA patients by immunohistochemistry, albeit the tissues analyzed were from a small number of RA patients. The same study demonstrated some connection between HHV-6 infection and RA disease activity [ 98 ]. Conversely, another study analyzing RA patients’ synovial fluid could not detect HHV-6 DNA [ 99 ].…”
Section: Autoimmune Connective Tissue Diseasesmentioning
confidence: 97%
“…Another study demonstrated that HHV-6 DNA could be detected in synovial tissues and fluid, and antigens could be visualized in synovial tissues of RA patients by immunohistochemistry, albeit the tissues analyzed were from a small number of RA patients. The same study demonstrated some connection between HHV-6 infection and RA disease activity [ 98 ]. Conversely, another study analyzing RA patients’ synovial fluid could not detect HHV-6 DNA [ 99 ].…”
Section: Autoimmune Connective Tissue Diseasesmentioning
confidence: 97%
“…The results of several studies have confirmed the presence of human herpesvirus 6 (HHV-6) and 7 (HHV-7) DNA and viral antigens by polymerase chain reaction (PCR) techniques, in situ hybridization, immunohistochemistry, and electron microscopy in blood plasma, peripheral blood mononuclear cells, the brain, and skin [ 25 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, our earlier study reported on the presence of human HHV-6 and HHV-7 infection markers in synovial fluid and synovial tissues of rheumatoid arthritis (RA)-affected patients [ 31 ]. HHV-6A, HHV-6B, and HHV-7 are genetically related to human cytomegalovirus (HCMV) constituting the β-herpesvirus subfamily [ 22 , 32 ].…”
Section: Introductionmentioning
confidence: 99%